2004
DOI: 10.2169/internalmedicine.43.960
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Insipidus from Neurosarcoidosis: Long-term Follow-up for More than Eight Years

Abstract: Four patients with sarcoidosis presented as hypothalamic-hypophyseal syndrome including diabetes insipidus (DI) were followed up for more than 8 years from the onset of clinical manifestation. The mean age was 26 years, male : female ratio was 3 : 1 and the mean disease duration of 10 years. All patients had hypogonadism, hyperprolactinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 17 publications
(13 reference statements)
2
42
1
3
Order By: Relevance
“…There have been few case reports that diabetes insipidus could be cured in this situation, except for one spontaneous remission case (11). It has been considered that anterior pituitary function is difficult to restore, because hypopituitarism is not improved although the thickened pituitary stalk and enlarged pituitary gland return to their normal shapes after steroid treatment (3,12). However, a few case reports have shown that steroid therapy is able to partially improve anterior pituitary hormone secretion, which was confirmed by an endocrine provocation test (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…There have been few case reports that diabetes insipidus could be cured in this situation, except for one spontaneous remission case (11). It has been considered that anterior pituitary function is difficult to restore, because hypopituitarism is not improved although the thickened pituitary stalk and enlarged pituitary gland return to their normal shapes after steroid treatment (3,12). However, a few case reports have shown that steroid therapy is able to partially improve anterior pituitary hormone secretion, which was confirmed by an endocrine provocation test (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic effects of corticosteroids on hypothalamo-pituitary involvement due to sarcoidosis have been proposed [19]. In general, the effectiveness to restore anterior pituitary function and diabetes insipidus is unexpected [20], although a case of neurosarcoidosis showing complete resolution of the suprasellar mass as well as recovery of concurrent hypogonadism is documented [21]. Clinical courses of sarcoidosis are varied and advanced disease with extensive granulomatous involvement leads to irreversible neurological deficit [22].…”
Section: Discussionmentioning
confidence: 99%
“…In CNS sarcoidosis, the delay of initial treatment of steroid easily leads to the irreversible CDI (9,10). Thus the prompt diagnosis is important.…”
Section: Polyuria and Polydipsia Are Common Presenting Features Of mentioning
confidence: 99%
“…Although the prognosis of CNS sarcoidosis with/without steroid treatments is poor (9,10) (Fig. 4) (Fig.…”
Section: Polyuria and Polydipsia Are Common Presenting Features Of mentioning
confidence: 99%